Effect of multimodal therapy on children with attention deficit hyperactivity disorder - Mhtare, Priti; Gajre, Mona; Karia, Sagar; Chheda, Nidhi; Saroj, Dinesh; Sousa, Avinash De (International Journal of Contemporary Pediatrics, 2017)
Background: Attention deficit hyperactivity disorder (ADHD) is the most common neurobehavioral disorder affecting school aged children. Multimodal treatment is the most effective form of treatment which includes multiple elements like parent and child education about diagnosis and treatment, specific behaviour management techniques, medications and appropriate educational programs. This study was planned to study effect of multimodal intervention i.e. medication along with behavioral modification therapy and occupational therapy given to children with ADHD. Methods: This was a longitudinal, prospective study carried out from January 2014 to October 2014, in which children coming to pediatric neuro-developmental centre and diagnosed as ADHD were included. Cognitive behavior therapy (CBT) was given along with required medications to these children. Improvement in symptoms was checked by Conner scale 3TM long form given to both parents and teachers. Results: 41 out of 50 children complied with our study and majority were of ADHD- combined type (92.6%). 31 out of 41 students achieved non-significant, T- score at the end of 6 months on Global score of Conner Scale. Conclusions: Multimodal intervention was found effective in treating children with ADHD.